Walter I. Wittmann (1918-1992) - Newton, George B. (ARCTIC, 1992)
Walter I. Wittmann, an arctic oceanographer and expert on sea ice, died at age 73 on 19 March 1992 . During a career that spanned nearly five decades, he was a prominent figure in many of the early efforts to describe, understand, and predict the behavior of arctic sea ice and icebergs. He resided in the Washington, D.C., area, where he had been the director of the Polar Oceanography Division at the Naval Oceanographic Office (NAVOCEANO) prior to his retirement from the federal government in 1974. . He established the first methodologies used in the United States for the observation and prediction of icebergs and sea ice. He spent time in Halifax, Nova Scotia, assisting the Canadians in organizing their own ice observing and forecasting capability, which evolved into the Canadian Ice Centre now located in Ottawa. Walter Wittmann served as head of U.S. Naval Oceanographic Office's Sea Ice Branch and later as the initial director of the Polar Oceanography Division from 1962 through 1974. . During the period 1974-78, Mr. Wittmann was affiliated with the Arctic Institute of North America. He formulated methodologies for sea ice prediction and outlined and implemented feasibility studies concerning the effects of ice and environment on the conduct of various types of oil and gas exploration and activity in ice-covered environments. He also served for a number of years as a staff scientist with the U.S. Navy's Arctic Submarine Laboratory. During the 1980s, he worked for Sea Ice Consultants, Inc., and Integrated Systems Analysts as a sea ice consultant. The list of Mr. Wittmann's scientific writings and other professional contributions is a long one, but he leaves a legacy that is much broader than his own record indicates. While at NAVOCEANO he trained many of the current generation of arctic scientists in the study of a region that most never suspected would become their career focus. . He managed to combine personal concern with technical understanding in a way that made lasting impressions on those who worked under ...